Prinsip Keadilan UU No. 48 Tahun 2009 Kekuasaan Kehakiman dan H.R Abu Dawud No. 3573 - Irawan, Zahran Abhipraya; Arifin, Tajul (Journal of Literature Review, 2025)
The principle of justice is a fundamental foundation in legal systems, both in positive law and Islamic law. This article aims to examine the principle of justice as regulated in Law Number 48 of 2009 concerning Judicial Power and the hadith of the Prophet Muhammad (peace be upon him) narrated by Abu Dawud No. 3573. This study uses a normative-comparative approach with qualitative analysis of the legal text and the hadith. The findings show that both legal sources place justice as the central goal of judicial practice. In positive law, justice is supported by legal systems and procedures, while in Islamic law, it is upheld by the moral and spiritual responsibility of the judge. Integrating both perspectives may strengthen the integrity of the Indonesian judicial system